Survei Tingkat Kebugaran Jasmani Pada Siswa Kelas X Teknik Komputer Dan Jaringan Di Smk Negeri 5 Palu - Fery Lamudo; Muhammad Ismail; Moh. Ifkhal Sianto; Jumain Jumain; Delvi Kristanti Liloi (Jurnal Porkes, 2026)
Physical fitness is an important indicator in supporting the optimization of the learning process; however, the nature of the Computer and Network Engineering (TKJ) program which is dominated by computer-based activities has the potential to increase sedentary behavior and affect students’ physical fitness. This study aims to measure and describe the physical fitness levels of 10th-grade TKJ students at SMK Negeri 5 Palu using the Indonesian Physical Fitness Test (TKJI) for ages 16–19. The study employed a quantitative approach using a survey method and a descriptive design. The population consisted of 35 students, all of whom were included in the sample through total sampling. The assessment instruments consisted of the 60-meter run, pull-ups, sit-ups, vertical jump, and 1000-1200 meter run. Data were analyzed using descriptive statistics. The results showed that the majority of students fell into the “good” category for nearly all components, with the highest percentages in the 1,000-1,200-meter run (54.28%), the 60-meter dash and vertical jump (48.57%), and sit-ups (42.85%), while pull-ups were predominantly in the “moderate” category (40%). In general, the students’ physical fitness levels were in the “fairly good” category, although there were still variations in ability across each component, particularly in arm strength and endurance. This study is expected to serve as a basis for physical education teachers and schools in developing more targeted physical fitness training programs tailored to the characteristics of the students.